A Longitudinal Investigation of Social Functioning in Children with Neurofibromatosis Type 1 - (:unkn) unknown (My University, 2019)
Social difficulties are commonly reported by parents and teachers of children with neurofibromatosis type 1 (NF1) and can impact a child’s social relationships. Investigations of social functioning in children with NF1 during early childhood are scarce, with most studies focusing on school age. This study aims to characterize the emergence of social skills challenges for children with NF1, with a special focus on the stability of social skills longitudinally and the interrelations of social skills with ADHD symptomatology and cognitive function. Participants included children with NF1 who were assessed longitudinally during early childhood from the ages of 3-6 years (T1; n = 50; M= 3.96, SD= 1.05) and from early childhood to school age (n = 25) and their parents. Forty children (T2; ages 9-13; M= 10.90, SD= 1.59) were assessed during school age. Young children and school age children with NF1 experienced social skills difficulties in comparison to the normative mean. Social skills were relatively stable throughout early childhood and school age with no differences in mean social skills across age. Social skills at the end of early childhood predicted school age social skills. ADHD symptomatology showed significant negative relations with social skills concurrently and early childhood inattentive symptoms predicted school age social skills. GCA showed a weak relation to social skills during early childhood. Cognitive functioning was not related to social skills concurrently during school age or across time. Overall, these findings contribute to the limited NF1 social functioning literature, especially in early childhood, and help provide a target for early and effective intervention.
Keywords: longitudinal; Neurofibromatosis type 1; NF1; social functioning; social skills